Innovative findings about ferrous oxalate dihydrate crystallization in simulated dihydrate phosphoric acid product - Abdel-Ghafar, H M (Water science and technology : a journal of the International Association on Water Pollution Research, 2018)
The basic fundamentals of ferrous oxalate dihydrate (FeC2O4.2H2O) crystallization including supersaturation, nucleation and crystal growth in simulated dihydrate phosphoric acid product with and without cetyl pyridinium chloride (CPC) additive were studied. Oxalic acid and ferrous sulfate heptahydrate crystals were mixed with dilute phosphoric acid (28% P2O5) at 60 °C and the turbidity of the reaction mixture was measured at different time intervals. Induction time of ferrous oxalate dihydrate crystals was calculated at different supersaturation ratios ranging from 2.5 to 6.7. With increasing the supersaturation ratio, the induction time decreased. The nucleation rates are 46.4 × 1028 nuclei cm-3 s-1 and 50.2 × 1028 nuclei cm-3 s-1 at supersaturation ratio 6.7 with and without CPC addition, respectively. The surface energy increases with CPC addition compared to the baseline. In addition, the formed crystals are modified from cubic shape to rod-like shape with increasing CPC dose